Pediatric Stroke Outcome Measure: Predictor of Multiple Impairments in Childhood Stroke. (November 2014) - Lo, Warren; Gordon, Anne L.; Hajek, Christine; Gomes, Alison; Greenham, Mardee; Anderson, Vicki; Yeates, Keith O.; Mackay, Mark T.
The ability to anticipate deficits would help with implementation of interventions for children affected by stroke. The Pediatric Stroke Outcome Measure (Measure) measures neurological impairment after stroke, but there has been little research examining the relationship between the Measure and functional outcomes. We hypothesized the Measure correlates with cognitive and behavioral outcomes. Thirty-six children with stroke were assessed with the Measure, and tested for cognitive ability, problem behavior, adaptive behavior, and social participation. We examined the correlation between the total Measure and outcomes and determined how subscale scores associated with outcomes. Higher total Measure scores correlated with poorer outcomes in cognitive ability, problem behaviors, adaptive behaviors, and social participation. Specific subscale scores correlated with poorer outcomes in multiple domains. The total Measure can be used to anticipate poor outcomes in multiple domains after stroke and can help the clinician in the treatment of children as they recover.